STABILITY INDEX OF THE TREATED WATER FROM ALKARKH AND AL-RASHEED WATER TREATMENT PLANTS IN BAGHDAD CITY (Journal of Engineering, 2009)
An analysis was performed on the treated water from two water treatment plants in Baghdadcity. This analysis was used to evaluate the stability of the treated water from these plants andthat will flow in the distribution system to consider its corrosivity. The variation in waterstability with time and distance from the north to the south of Baghdad was indicated. Theanalysis showed that the flowing water in the distribution system in Baghdad is corrosive to verycorrosive water by calculating Ryznar stability index (RI). In Al- Karkh WTP in the north, RImaximum ranged between 7.958 to 9.403 where RI minimum ranged between 7.03 to 7.915.Where in the south Al-Rasheed WTP, RI maximum ranged between 7.119 to 8.63 and RIminimum ranged 6.679 to 7.994. The corrositivity of water decreased in the water flowing downstream. The water quality parameters affecting RI was discussed which were calcium, alkalinity,total dissolved solids and pH.